2019
DOI: 10.1155/2019/5924580
|View full text |Cite
|
Sign up to set email alerts
|

Model Test and Numerical Analysis on the Deformation and Stability of a Landslide Subjected to Reservoir Filling

Abstract: Reservoir filling can affect the landslide stability and cause the landslide deformation within the reservoir area. In this paper, a physical model test and a series of numerical analyses were combined to investigate the landslide deformation and stability under reservoir filling. The surface deformation, deep displacement, and pore water pressure were recorded during the physical model test. In the model test, the increasing period of the pore water pressure inside the landslide is proposed to be a critical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Luo et al [15] conducted a model test of the failure process of a soil slope with different angles under the drawdown of the water level and found that the position of the slide surface became deeper with the increase of the slope angles. Hu et al [16] carried out laboratory model tests of the deformation mechanism of landslides under water level fluctuations and concluded that the increase of pore water pressure inside the slope soil was the key factor triggering the slope failure. Yang et al [17] studied the failure process of a silt slope under the sudden drop of reservoir water level and found that failure mode and crack propagation were closely related to the mechanical properties of unsaturated soil.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [15] conducted a model test of the failure process of a soil slope with different angles under the drawdown of the water level and found that the position of the slide surface became deeper with the increase of the slope angles. Hu et al [16] carried out laboratory model tests of the deformation mechanism of landslides under water level fluctuations and concluded that the increase of pore water pressure inside the slope soil was the key factor triggering the slope failure. Yang et al [17] studied the failure process of a silt slope under the sudden drop of reservoir water level and found that failure mode and crack propagation were closely related to the mechanical properties of unsaturated soil.…”
Section: Introductionmentioning
confidence: 99%
“…PCA is used to process the original data, and the six influence factors are reduced into four main influence factors, which reduce the complexity of the algorithm; RVM is applied to establish the mapping relationship between influence factors and slope stability after dimension reduction, so as to predict slope stability. The PCA-RVM model simplifies the complex problems and makes the prediction process more efficient and concise (2) The results show that the PCA-RVM model is superior to the GEP model and the RVM model in terms of mean square error and mean relative error in predicting rock slope stability, with higher accuracy and lower discreteness. In the aspect of slope stability, the PCA-RVM model has high credibility, and the predicted value is basically consistent with the actual value, which can provide reference for the prevention and control of slope disasters…”
Section: Discussionmentioning
confidence: 96%
“…Slope sliding is a common geological disaster phenomenon, which has great harm. Once it occurs, it will seriously threaten people's lives and property and various engineering safety, causing great losses [1,2]. Some slope instability disasters, which are located in China, are shown in Figure1.…”
Section: Introductionmentioning
confidence: 99%
“…Within a relatively short period, the sand structure is irreversibly deformed due to the loading and unloading of water, and the structure is rearranged. With the increase in the pore water pressure, matrix suction is reduced, and the effective stress on the sand framework decreases, which reduces the shear strength and stability of the landslide [67,68]. However, a rise in water level generates water pressure, which provides a supporting force acting on the landslide surface, in turn increasing its resistance to movement and increasing the stability of the slopes [66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%